Urgensi Reformasi Hukum Kepailitan dalam Memitigasi Risiko Sistemik terhadap Stabilitas Makroekonomi - Sudhana, Harry; Muhammad Ruhunussa; Raden Giri; Raineldis Bero; Yusfika Ely Nur Afifah; Edi Mulyadi (IJESM Indonesian Journal of Economics and Strategic Management, 2025)
This study examines the urgency of bankruptcy law reform within the framework of mitigating systemic risks that threaten macroeconomic stability. As theoretical research, this article analyzes the correlation between the efficiency of insolvency regimes and macroeconomic variables such as investment, banking sector health, and resource allocation. The findings indicate that a rigid bankruptcy law, which is merely oriented toward formal-legalistic aspects, can trigger the "zombie firms" phenomenon, which hinders national productivity and exacerbates financial contagion during crises. Legal reform is necessary to shift the paradigm from a private debt-settlement mechanism to an economic policy instrument capable of distinguishing between temporary liquidity shocks and fundamental insolvency. In conclusion, strengthening debt restructuring mechanisms and synchronizing judicial authorities with macroprudential policies are crucial for building economic resilience. Legal uncertainty in bankruptcy proceedings not only harms the parties involved but also escalates systemic risks that can destabilize overall national economic growth.